Nature play at home : creating outdoor spaces that connect children with the natural world - Striniste, Nancy, 1958- (Timber Press, Inc., 2019)
Access to technology has created a generation of children who are more plugged in than ever before<U+2014>often with negative consequences. But there is a solution. Unrestricted outdoor play helps reduce stress, improve health, and enhance creativity, learning, and attention span. In Nature Play at Home, Nancy Striniste gives you the tools you need to make outdoor adventures possible in your own backyard. With hundreds of inspiring ideas and illustrated, step-by-step projects, this hardworking book details how to create playspaces that use natural materials<U+2014>like logs, boulders, sand, water, and plants of all kinds. Projects include hillside slides, seating circles, sand pits, and more.